Investigating the Pedagogic Competence of Pre-Service High School Teachers in Terms of Learning Planning Abilities - Fathor Rakhman; Rosmiati; Muhammad Satriawan (Studies in Learning and Teaching, 2024)
One factor that determines teachers' success in teaching is the teacher's ability to plan lessons. Careful and good lesson planning can help create an effective learning environment, maximize students' potential, and increase their learning success. It also assists teachers in teaching in a more structured and directed manner, positively impacting student learning outcomes. Therefore, the purpose of this study was to investigate the ability of pre-service high school teachers to plan lessons based on the Merdeka Curriculum. This research is a descriptive study with 37 pre-service high school teachers as subjects. Data were collected using angles, portfolios, and interview sheets which were then analyzed using quantitative and qualitative approaches. Based on the results of data analysis, it was found that the pedagogic competence of pre-service high school teachers in terms of the ability to plan lessons according to the Merdeka Curriculum was 23% at a low level, 47% at a medium level, and 30% at a high level. Therefore, pre-service high school teacher's ability to plan to learn needs to be improved, especially in learning design scenarios and assessments. The results of this research contribute as input to related parties, in this case, the Institute of teacher education and Training Institutes, in developing teacher education and training programs that are relevant and adaptive to current educational developments.